PEMANFAATAN MEDIA TIK TUTORIAL SEBAGAI SUPLEMEN DEMONSTRASI PADA PEMBELAJARAN ALAT UKUR DI SMP - David Nissius Siregar; Eko Suyanto; Feriansyah Sesunan (Jurnal Pembelajaran Fisika, 2014)
The purposes of this study were: to determine the increasing of cognitive learning outcomes of students, to build the students Science Process Skills, to create character of students, to build activity, to build the attitudes of students toward the use of ICT media as a supplement tutorial demonstration on measuring instruments . This research was conducted in the first semester of the academic year 2013/2014 at the Junior High School 1 Pesisir Selatan, West Lampung. The population of this research was every students of class VII and the sample was class VII A of 26 students. The research design used is a One-Shot Case Study. The results is that by using the tutorial ICT media as a supplement to demonstrate on measuring instruments learning there is an increase in cognitive learning outcomes of students, to build KPS students, to create the character of the students, to build the activities of the students, and to build a positive attitudes of the students.Penelitian ini bertujuan untuk: mengetahui pertambahan hasil belajar ranah kognitif, membangun KPS, menciptakan karakter, membangun aktivitas, membangun sikap siswa terhadap pemanfaatan media TIK Tutorial sebagai suplemen demonstrasi pada alat ukur. Penelitian ini dilakukan di semester ganjil pada tahun ajaran 2013/2014 di SMP Negeri 1 Pesisir Selatan, Lampung Barat. Populasi penelitian adalah seluruh siswa kelas VII sedangkan sampel yaitu kelas VII A dengan jumlah 26 siswa. Pemilihan sampel dilakukan dengan memilih 1 kelas secara random dari 4 kelas yang ada. Hasil penelitian menggunakan media TIK tutorial sebagai suplemen demonstrasi pada pembelajaran alat ukur terdapat peningkatan hasil belajar ranah kognitif siswa, dapat membangun KPS siswa, dapat menciptakan karakter siswa, dapat membangun aktivitas siswa, dan dapat membangun sikap positif siswa.Kata kunci: aktivitas, hasil belajar, karakter, keterampilan proses sains, media, ranah kognitif, sikap